Pemberdayaan Masyarakat Melalui Pemanfaatan Rptra Di Kota Administrasi Jakarta Utara - Amalia, Rizki; Rachmawati, Ira; Ilham, Muh. (UIR Press, 2024)
This research aims to determine community empowerment through the use of RPTRAs, analyze the supporting and inhibiting factors faced in community empowerment in the use of RPTRAs and examine the strategies used for community empowerment in the use of RPTRAs in the Administrative City of North Jakarta. The research method used is qualitative research using the case study method. By adapting the concept of community empowerment proposed by Sumadyo (2001) and Toto Mardikanto (2023). The data in this research was obtained from triangulation of interview results and documentation. Data analysis in this research uses the Miles and Huberman model consisting of data reduction, data presentation, drawing conclusions/verification. Research results Community empowerment through the use of RPTRAs in the North Jakarta Administrative City has gone well in terms of 4 dimensions, namely the Human Development, Business Development, Environmental Development and Institutional Development dimensions. Human development is realized through various activities. Business development is carried out by creating job training programs that involve collaboration between agencies, holding workshops, seminars and product marketing training from activities such as growing hydroponic vegetables. Community development shows an active role through a series of activities such as tree planting, recycling programs and efforts to keep the environment clean. Institutional development is carried out through PIK Keluarga, BKB PAUD, Posyandu, Food Security and Gross Mart activities at RPTRA. Supporting factors are a) the existence of interactive services and facilities, b) the presence of a Posyandu which provides comfort, c) a safe environment, d) free health checks, e) support from health workers from the local health center, f) the existence of a Grossmart RPTRA for storing community products for increasing family income and supporting local MSMEs, g) adequate facilities, h) large fields and i) education on BKB PAUD activities in RPTRA. Inhibiting factors are the lack of solutions and lack of socialization regarding family PIK services in RPTRAs, limited infrastructure for BKB PAUD activities, lack of public understanding about Family PIK Services in RPTRAs, obstacles in developing food security activities, lack of awareness and availability of quality plant seeds and lack of training and understanding of the importance of food security. The efforts made are educational and social activities by community members, training programs and regional government collaboration, varied activities by RPTRA managers, inclusive community development, increasing the role of women and community initiatives involving levels of society.